Activation of RyR2 by class I kinase inhibitors - Chakraborty, A. D. (2019)
Kinase inhibitors are a common treatment for cancer. Class I kinase inhibitors that target the ATP-binding pocket are particularly prevalent. Many of these compounds are cardiotoxic and can cause arrhythmias. Spontaneous release of Ca2+ via cardiac ryanodine receptors (RyR2), through a process termed store overload-induced Ca2+ release (SOICR), is a common mechanism underlying arrhythmia. We explored whether class I kinase inhibitors could modify the activity of RyR2 and trigger SOICR to determine if this contributes to the cardiotoxic nature of these compounds.